Analisis Dampak Kebijakan Ekspor terhadap PDB, Pengangguran, dan Inflasi di Indonesia - Andriansyah, Umar; Maharani, Rafaela Suryadiva Indira; Zahra, Rasya Az; Herlan, Mumtahanah Ceisa; Arbain, Nabil; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
International trade provides opportunities for every country to export and import the commodities it produces in order to fulfill the need for goods and services. Goods and services that cannot be obtained domestically can be obtained through international trade. This can be increase foreign exchange for exporting countries. This study aims to determine the impact of export policies on GDP, unemployment, and inflation in Indonesia. The data used in this research comes from the World Development Indicators (WDI) and Central Bureau of Statistics (BPS) from 1986 to 2021. The analysis used is a system of simultaneous equations model using the Two-Stage Least Square (2SLS) estimation method. Based on the research result, there is a positive relationship between export and GDP. In addition, exports also indirectly affect unemployment and inflation through GDP. From the simulation results, an increase in export will encourage economic growth, increase the unemployment rate, and reduce the inflation rate.